THE INFLUENCE OF HUMAN RESOURCES COMPETENCE AND DISPOSITION ON HANDLING THE TRAFFIC CONGESTION PROBLEMS IN MENGKRENG - Hendry Ibnu Indarto (Universitas Airlangga, 2023)
There is a positive influence of human resource competence and disposition on the effectiveness of policy implementation from the results of the Traffic Forum implementation. As for the percentage of simultaneous influence of independent variables on the effectiveness of policy implementation from the results of the implementation of the traffic forum, it is known that the HR Competence and Disposition variables simultaneously (together) affect the effectiveness of the policy implementation variable from the results of the Traffic Forum implementation of 86.5%. While the rest (100% - 86.5% = 13.5%) is influenced by other variables outside the regression equation or variables not examined.